2016
DOI: 10.3390/ma9040246
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Electrodeposition Mode for Porous MnO2/Ni Foam Composite for Asymmetric Supercapacitors

Abstract: Three kinds of MnO2/Ni foam composite electrode with hierarchical meso-macroporous structures were prepared using potentiodynamic (PD), potentiostatic (PS), and a combination of PS and PD(PS + PD) modes of electrodeposition. The electrodeposition mode markedly influenced the surface morphological, textural, and supercapacitive properties of the MnO2/Ni electrodes. The supercapacitive performance of the MnO2/Ni electrode obtained via PS + PD(PS + PD(MnO2/Ni)) was found to be superior to those of MnO2/Ni electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Electrodeposition has been developed and used widely for producing metal oxides and hydroxides since it can be carried out under mild condition at room temperature . The electrodeposition produces with different shapes and sizes can be easily obtained through controlling current, potential, solution concentration or time.…”
Section: Resultsmentioning
confidence: 99%
“…Electrodeposition has been developed and used widely for producing metal oxides and hydroxides since it can be carried out under mild condition at room temperature . The electrodeposition produces with different shapes and sizes can be easily obtained through controlling current, potential, solution concentration or time.…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical measurements were carried out in both three-electrode configuration for electrodes and two-electrode configuration for symmetric supercapacitors. In the three-electrode setup, the SRAC/Ni was as the working electrode, a Pt foil as the counter electrode, a saturated calomel electrode (SCE) as the reference electrode, and 6 M LiNO 3 aqueous solution as the electrolyte [ 40 ]. The cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and galvanostatic charge–discharge (GCD) measurements were performed with an electrochemical workstation (6273E, CH Instruments, USA).…”
Section: Methodsmentioning
confidence: 99%
“…26 Macroporous manganese oxide electrodes were prepared by template-assisted electrodeposition showing specific capacitance 60% higher than that obtained from flat surfaces, without loss of capacitance even after 1000 cycles. 27 In addition, Tsai et al 28 reported the influence of the electrodeposition method on the morphology and capacitive properties of the electrodes. In this work, it was described the preparation of composites based on MnO 2 /Ni foams by three different methods: potentiodynamic (PD), potentiostatic (PS) and a combination of them (PS + PD ) and long cycle life.…”
Section: Introductionmentioning
confidence: 99%
“…27 In addition, Tsai et al 28 reported the influence of the electrodeposition method on the morphology and capacitive properties of the electrodes. In this work, it was described the preparation of composites based on MnO 2 /Ni foams by three different methods: potentiodynamic (PD), potentiostatic (PS) and a combination of them (PS + PD).…”
mentioning
confidence: 99%
See 1 more Smart Citation